Cross-talk between the cytokinin, auxin, and gibberellin regulatory networks in determining parthenocarpy in cucumber - Mandal, Neha Kumari; Kumari, Khushboo; Kundu, Aditi; Arora, Ajay; Bhowmick, Prolay K.; Iquebal, Mir Asif; Jaiswal, Sarika; Behera, Tusar Kanti; Munshi, A. D.; Dey, Shyam S. (Frontiers in Genetics, 2022)
Cucumber is a model plant for studying parthenocarpy with abundant slicing- and pickling-type germplasm. This study was undertaken to understand the role of the important cytokines (CKs), auxin (AUX) and gibberellin (GA) biosynthesis and degradation genes for the induction of parthenocarpy in slicing and pickling germplasm. Two genotypes of gynoecious parthenocarpic cucumber, PPC-6 and DG-8, along with an MABC-derived gynoecious non-parthenocarpic line, IMPU-1, were evaluated in this study. The slicing and pickling cucumber genotypes PPC-6 and DG-8 were strongly parthenocarpic in nature and set fruit normally without pollination. Endogenous auxin and gibberellin were significantly higher in parthenocarpic than non-parthenocarpic genotypes, whereas the concentration of cytokinins varied among the genotypes at different developmental stages. However, the exogenous application of Zeatin and IAA + Zeatin was effective in inducing parthenocarpic fruit in IMPU-1. Expression analysis with important CK, AUX, and GA biosynthesis-related genes was conducted in IMPU-1, PPC-6, and DG-8. The expression of the CK synthase, IPT, IPT3, PaO, LOG1, LOG2, CYP735A1, and CYP735A2 was up-regulated in the parthenocarpic genotypes. Among the transcription factor response regulators (RRs), positive regulation of CSRR8/9b, CSRR8/9d, CSRR8/9e, and CSRR16/17 and negative feedback of the CK signalling genes, such as CsRR3/4a, CsRR3/4b, CsRR8/9a, and CsRR8/9c, were recorded in the parthenocarpic lines. Homeostasis between cytokinin biosynthesis and degradation genes such as CK oxidases (CKXs) and CK dehydrogenase resulted in a non-significant difference in the endogenous CK concentration in the parthenocarpic and non-parthenocarpic genotypes. In addition, up-regulation of the key auxin-inducing proteins and GA biosynthesis genes indicated their crucial role in the parthenocarpic fruit set of cucumber. This study establishes the critical role of the CKs, AUX, and GA regulatory networks and their cross-talk in determining parthenocarpy in slicing and pickling cucumber genotypes.